AN ALTERNATIVE APPROACH TO MEET BEEF SELF-SUFFICIENCY IN WEST PAPUA - Hartono, S.; Widayati, T.W. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The main objective of this research is to present an alternative approach to meet beef selfsufficiencyin West Papua, Indonesia. It mainly focuses on calculating the needed number of productivecows to enhance beef production in the province. Out of the total farmer households in Manokwari,Indonesia, 189 farmer-respondents were selected as samples of the study. Selection of the sample wasbased on the number of cattle kept in every age group (less than one (<1) year old; one to two (1-2)years old, and more than two (>2) years old and the number of productive cows. Secondary data camefrom the time series data of the number of slaughtered cattle vis-à-vis the population of all districts inWest Papua Province from 1980-2008. Data were analyzed using the Partial Adjustment Model (PAM)and Ordinary Least Square (OLS) method. Results of the study showed that beef self-sufficiency in WestPapua depend on the availability of the number of productive cows to produce ready-slaughtered-bull inthe previous year. Particularly for West Papua, to produce one unit of bull in the tth –year, with theassumption that cattle mortality is 4.92%, a number of 2.38 animal units AU of productive cows must beprovided in the previous two (2) years.